"Locus sententiosus" w komedii rzymskiej Lucjusza Afraniusza - Stankiewicz, Lucyna (Collectanea Philologica, 2004)
The paper concerns some fragments of the Roman comedy written by Lucius Afranius, in which sententiae or a tendency to sententiousness can be found.